Post-qualitative design research: Negotiating serendipity and risking the colonised self - Perold-Bull, Karolien; Costandius, Elmarie (Critical Studies in Teaching and Learning, 2023)
The research discussed in this paper aimed to explore design education in the context of transformation in South African higher education through practising design research/education geared at productive change within a specific institution. Through experimentation with a postqualitative methodological approach, processes of subjectification that transpired throughout the doing of a specific case of design/research/teaching in the context of the institution’s Visual Communication Design curriculum were critically negotiated. Experimentation with representational praxis in ways that challenged its traditional semiotic function allowed space and time for subjects to become more attuned to recognising and responding to serendipitous moments within their situated present. It can, consequently, be argued that the more such moments become felt through everyday design education and practice, the more receptive individuals can become to the potential for productive future change.